2021
DOI: 10.3390/su13052455
|View full text |Cite
|
Sign up to set email alerts
|

Community Participation and Residents’ Support for Tourism Development in Ancient Villages: The Mediating Role of Perceptions of Conflicts in the Tourism Community

Abstract: As increasing numbers of tourists have begun to visit ancient villages, conflicts between tourism development and residents have become one of the main challenges to the sustainable development of the tourism community. This research explores the relationship between community participation and residents’ support for tourism development in an ancient village. This study surveyed 249 indigenous residents living in Whampoa Village, Guangzhou, China. The findings show that community participation in tourism devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 60 publications
0
27
0
4
Order By: Relevance
“…Ngebel tourism, through the dolanngebel.com website, shows an ideal example of e-government technology implementation. E-government can also be termed an effort to implement web-based development to improve public services (M. Wang, Jiang, Xu, & Guo, 2021). Thus, e -government can be interpreted as a government initiative to improve the quality of public services using information technology (web) (Uyar et al, 2021).…”
Section: Application Of E-government In Tourismmentioning
confidence: 99%
“…Ngebel tourism, through the dolanngebel.com website, shows an ideal example of e-government technology implementation. E-government can also be termed an effort to implement web-based development to improve public services (M. Wang, Jiang, Xu, & Guo, 2021). Thus, e -government can be interpreted as a government initiative to improve the quality of public services using information technology (web) (Uyar et al, 2021).…”
Section: Application Of E-government In Tourismmentioning
confidence: 99%
“…[7]Moreover, if local residents participate in the process of decision making, they may have a more positive attitude towards the tourism development of ancient villages and they may try their best to preserve the traditional way of life. [8]…”
Section: Community Participation In Tourism Developmentmentioning
confidence: 99%
“…Rural tourism is a significant step forward in the accomplishment of ethnic rural rejuvenation. Using the Shiyi Qiang Stockaded hamlet in Beichuan Qiang Autonomous county of Sichuan province as a sample, Wang et al [51] investigated the relationship between rural tourism and rural communities using the notion of community empowerment. They revealed that rural tourism could improve community cohesiveness.…”
Section: Effect Of Rural Tourism On Rural Community Development In Chinamentioning
confidence: 99%